Native hosts and parasitoids associated with anastrepha fractura and other anastrepha species (diptera: Tephritidae) in the Brazilian Amazon - Dutra, Vivian Siqueira; Ronchi-Teles, Beatriz; Garcia, Marcos Vinicius Bastos; Adaime, Ricardo; Silva, Janisete Gomes (Florida Entomologist, 2013)
A new natural host for Anastrepha fractura Stone, Salacia sp., is reported for the first time in Brazil. Parasitoids attacking A. fractura are also reported. We also report Anastrepha distincta Greene infesting Inga cinnamomea in Brazil for the first time. New associations between Anastrepha species and parasitoids are also reported.
Keywords: Insect; Native Species; New Record; New Species; Parasite Infestation; Parasitoid; Amazonas